2012
DOI: 10.1016/j.neuroscience.2012.08.023
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase F-box/G-domain protein 1 promotes the degradation of the disease-linked protein torsinA through the ubiquitin–proteasome pathway and macroautophagy

Abstract: DYT1 dystonia is a dominantly inherited, disabling neurological disorder with low penetrance that is caused by the deletion of a glutamic acid (ΔE) in the protein torsinA. We previously showed that torsinA(wt) is degraded through macroautophagy while torsinA(ΔE) is targeted to the ubiquitin proteasome pathway (UPP). The different catabolism of torsinA(wt) and (ΔE) potentially modulates torsinA(wt):torsinA(ΔE) stoichiometry. Therefore, gaining a mechanistic understanding on how the protein quality control machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…3 and 6). In addition, we obtained preliminary evidence that the proteins are ubiquitinated (data not shown), which is in agreement with a recent study showing that the E3 ubiquitin ligase, FBG1, is involved in the degradation of torsinA and torsinA⌬E (137). We also found that Kar2/BiP plays a pro-degradative role when the stability of torsinA and torsinA⌬E is compromised (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…3 and 6). In addition, we obtained preliminary evidence that the proteins are ubiquitinated (data not shown), which is in agreement with a recent study showing that the E3 ubiquitin ligase, FBG1, is involved in the degradation of torsinA and torsinA⌬E (137). We also found that Kar2/BiP plays a pro-degradative role when the stability of torsinA and torsinA⌬E is compromised (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…We asked if the ability of FBG1 to decrease A1AT-Z levels depended on its ubiquitin ligase function. To demonstrate whether the ubiquitin ligase activity of FBG1 is required to degrade A1AT-Z, we co-transfected A1AT-Z with pCMV, FLAG-tagged full-length FBG1 (FBG1), or a FLAG-tagged N-terminal deletion of FBG1 (FBG1ΔN), which deletes the SKP1 binding site, necessary for ubiquitination [ 25 ]. After 48 hours, cells were harvested and separated on SDS-PAGE stain-free gels ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, inhibition of the proteasome in this Atg5-deficient cells failed to increase A1AT-Z levels further indicating that the ALS pathway was the primary means of degradation of A1AT-Z [ 16 ]. Since past research has shown that FBG1 can function through both the UPP and ALS to clear misfolded proteins [ 25 ], we investigated whether FBG1 could degrade A1AT-Z through autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third point is the nature of the pathways and individual genes that are affected in Tor1a +/ΔE mice. Several of these had been implicated previously, for example, the eukaryotic translation initiation (Beauvais et al, 2018;Beauvais et al, 2019;Rittiner et al, 2016), protein ubiquitination pathway (Gordon et al, 2012;Nery et al, 2011) and cell cycle (Ledoux et al, 2013). Others were of particular interest, such as the mitochondrial function, intracellular trafficking and axonal guidance: they are involved in regulating neuronal functions including excitability.…”
Section: Implications Of Genotype-dependent Differences In Gene Exprementioning
confidence: 99%